1993
DOI: 10.1128/jvi.67.9.5187-5197.1993
|View full text |Cite
|
Sign up to set email alerts
|

Early events in immune evasion by the lentivirus maedi-visna occurring within infected lymphoid tissue

Abstract: Infections caused by lentiviruses, including human immunodeficiency virus, are characterized by slowly progressive disease in the presence of a virus-specific immune response. The earliest events in the vims-host interaction are likely to be important in determining disease establishment and progression, and the kinetics of these early events following lentiviral infection are described here. Lymphatic cannulation in the sheep has been used to monitor both the virus and the immune response in efferent lymph af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 53 publications
1
19
0
1
Order By: Relevance
“…Sheep are amenable to surgical lymphatic cannulation, and therefore such a detailed analysis is possible. Previously we have shown that major histocompatibility complex (MHC) class II-positive CD8 ϩ lymphoblasts exit the acutely infected lymph node via efferent lymph at about the same time that low frequencies of virus-infected cells are also detected leaving the node, disseminating the infection (4). It is now appreciated that the lymph nodes are major sites of HIV replication throughout the disease (11,31), and it is therefore likely that the virus-infected cells seen leaving acutely MVV-infected nodes are only a small proportion of the infected cells which remain in the node.…”
mentioning
confidence: 99%
“…Sheep are amenable to surgical lymphatic cannulation, and therefore such a detailed analysis is possible. Previously we have shown that major histocompatibility complex (MHC) class II-positive CD8 ϩ lymphoblasts exit the acutely infected lymph node via efferent lymph at about the same time that low frequencies of virus-infected cells are also detected leaving the node, disseminating the infection (4). It is now appreciated that the lymph nodes are major sites of HIV replication throughout the disease (11,31), and it is therefore likely that the virus-infected cells seen leaving acutely MVV-infected nodes are only a small proportion of the infected cells which remain in the node.…”
mentioning
confidence: 99%
“…The reason(s) for vaccine failure, poor efficacy and the increased disease in some instances remain obscure. An explanation may be stimulation defective T cell responses by the vaccines as suggested to occur during virus infection [54,55]. We believe understanding and countering the defective T cell responses in SRLV infections is important and it may lead eventually to effective vaccines.…”
Section: Controlmentioning
confidence: 99%
“…After infection with VMV, sheep mount an antiviral immune response (both antibody and T cell) but viral replication and dissemination still occur. An explanation put forward for this defect in VMV immune response has been the induction CD8+ T lymphocytes in a defective maturation state as also observed in T-cell-tropic lentiviruses [54]. The defective phenotype of CD8+ T lymphocytes in VMV infection involves expression of MHC class II DR and DQ molecules but not interlukin-2 receptor (IL-2R) and hence lacks lymphoproliferative and cytolytic activities [54].…”
Section: Diseasementioning
confidence: 99%
See 2 more Smart Citations